Metabolic and Oxidative Changes in the Fern Adiantum raddianum upon Foliar Application of Metals - Kováčik, Jozef; Husáková, Lenka; Babula, Petr; Matušíková, Ildikó (My University, 2022)
Cadmium (Cd) or nickel (Ni) were applied as a foliar spray (1 µM solution over one month) to mimic air pollution and to monitor metabolic responses and oxidative stress in the pteridophyte species. Exogenous metals did not affect the metal content of the soil and had relatively little effect on the essential elements in leaves or rhizomes. The amounts of Cd and Ni were similar in treated leaves (7.2 µg Cd or 5.3 µg Ni/g DW in mature leaves compared with 0.4 µg Cd or 1.2 µg Ni/g DW in the respective control leaves), but Ni was more abundant in rhizomes (56.6 µg Ni or 3.4 µg Cd/g DW), resulting in a higher Cd translocation and bioaccumulation factor. The theoretical calculation revealed that ca. 4% of Cd and 5.5% of Ni from the applied solution per plant/pot was absorbed. Excess Cd induced stronger ROS production followed by changes in SOD and CAT activities, whereas nitric oxide (NO) stimulation was less intense, as detected by confocal microscopy. The hadrocentric vascular bundles in the petioles also showed higher ROS and NO signals under metal excess. This may be a sign of increased ROS formation, and high correlations were observed. Proteins and amino acids were stimulated by Cd or Ni application in individual organs, whereas phenols and flavonols were almost unaffected. The data suggest that even low levels of exogenous metals induce an oxidative imbalance, although no visible damage is observed, and that the responses of ferns to metals are similar to those of seed plants or algae.
Metabolické a oxidační změny v kapradině Adiantum raddianum po aplikaci kovů
Keywords: antioxidant molecules; heavy metals; reactive oxygen species; soil pollution; antioxidační látky; těžké kovy; reaktivní formy kyslíku; znečištění půd